Unexpected low expression of platelet fibrinogen receptor in patients with chronic myeloproliferative neoplasms: how does it change with aspirin?. (2nd December 2019) - Lucchesi, Alessandro; Carloni, Silvia; De Matteis, Serena; Ghetti, Martina; Musuraca, Gerardo; Poggiaspalla, Monica; Augello, Accursio F.; Giordano, Giulio; Fattori, Pier P.; Martinelli, Giovanni; Napolitano, Roberta
Summary: This study was conducted to evaluate the expression of fibrinogen receptors on platelets of Philadelphia‐negative chronic myeloproliferative neoplasm (MPN) patients. We collected blood samples from 40 consecutive MPN patients and healthy volunteers. We performed flow cytometry analysis of P‐selectin expression and integrin beta‐3, activation of glycoprotein (GP) IIb/IIIa and fibrinogen receptor exposure (PAC‐1 binding). Surprisingly, we found a very low PAC‐1 binding capacity in MPN patients; however, the expression of PAC‐1 was almost completely recovered with aspirin intake. We hypothesize that the hypercoagulable states observed in MPN patients could depend on a primarily plasma‐driven impairment of fibrin turnover and thrombin generation.